Characterization and real‐time hybrid simulation testing of rolling pendulum isolation bearings with different surface treatments. (5th June 2022) - Covarrubias Vargas, Braulio A.; Harvey, P. Scott; Cao, Liang; Ricles, James M.; Al‐Subaihawi, Safwan; Villalobos Vega, Esteban
Abstract: Damage caused by earthquakes to buildings and their contents (e.g., sensitive equipment) can impact life safety and disrupt business operations following an event. Floor isolation systems (FISs) are a promising retrofit strategy for protecting vital building contents. In this study, real‐time hybrid simulation (RTHS) is utilized to experimentally incorporate multi‐scale (building–FIS–equipment) interactions. For this, an experimental setup representing one bearing of a rolling pendulum (RP) based FIS is studied—first through characterization tests and then through RTHS. A series of tests was conducted at the Natural Hazards Engineering Research Infrastructure (NHERI) Experimental Facility at Lehigh University. Multiple excitations were used to study the experimental setup under uni‐axial loading. Details of the experimental testbed and test protocols for the characterization and RTHS tests are presented, along with results from these tests, which focused on the effect of different rolling surface treatments for supplemental damping, the FIS–equipment and building–FIS interactions, and rigorous evaluation of different RP isolation bearing designs through RTHS.